PEREMPUAN DAN ENERGI BARU TERBARUKAN (EBT): PERAN KOALISI PEREMPUAN (KPI) KOTA SALATIGA DALAM MENINGKATKAN PEMBERDAYAAN ENERGI BARU TERBARUKAN (EBT) - Takayasa, Tika Ifrida; Bariklana, Muhammad Nuqlir; Azizah, Siti (JPW (Jurnal Politik Walisongo), 2021)
This study reveals the roles and strategies of women's organizations in the development of Renewable Energy (EBT) in Indonesia. The analysis of the study is based on examining the roles and strategies of the Indonesian Women's Coalition (KPI) in developing the empowerment of renewable energy in Salatiga City. This study was conducted using qualitative methods and the theory of the role of NGOs as an analysis framework. The important findings of this study reveal that the role of the Indonesian Women's Coalition (KPI) in Salatiga city in developing renewable energy (EBT) with Education Development, Participation and Empowerment, Advocacy, and Networking strategies. In conducting Advocacy, KPI using two approaches, a top-down approach through cooperation with the government and related agencies and the grassroots approach to listening to aspirations from below by establishing Balai Perempuan as a center for  Information complaints and advocacy on renewable energy (BP PIPA EBT), BP PIPA EBT is a milestone in the development of EBT in society. In the development of EBT, in the framework of the Strategic Partnership for Green and Inclusive Energy (SP-Energy), KPI also builds a network with similar organizations that are concerned with the development of renewable energy (EBT) in Indonesia. Studi ini mengkaji tentang Peran dan strategi organisasi perempuan dalam pengembangan Energi baru Terbarukan (EBT) di Indonesia. Analisis kajian dilakukan dengan mengkaji peran dan strategi Koalisi Perempuan Indonesia (KPI) dalam meningkatkan pemberdayaan energi baru terbarukan Kota Salatiga. Kajian ini dilakukan dengan menggunakan metode kualitatif dan teori Peran LSM sebagai kerangka analisis.  Hasil kajian ini menjelaskan bahwa peran Koaliasi Perempuan (KPI) di Kota Salatiga dalam pengembangan EBT menggunakan strategi Pengembangan Pendidikan, Partisipasi dan pemberdayaan, Advokasi serta Jaringan. Dalam Melakukan Advokasi KPI Kota Salatiga menggunakan dua pendekatan yaitu pendekatan dari atas ke bawah (top to bottom approach) dengan kerjasma dengan pemerintah dan dinas terkait  serta pendekatan akar rumput (grassroot approach)  untuk mendengarkan aspirasi dari bawah dengan membentuk Balai Perempuan sebagai Pusat  Informasi Pengaduan  dan advokasi (BP PIPA EBT) yang menjadi tonggak dalam pengembangan EBT di masyarakat. Dalam pengembangan EBT, KPI membangun jaringan bersama LSM yang juga mempunyai perhatian khusus mengenai isu energi dalam kerangka Strategic Partnership Green and Inclusive Energy (SP-Energy).